2018
DOI: 10.3390/md16050141
|View full text |Cite
|
Sign up to set email alerts
|

Haliotis discus discus Sialic Acid-Binding Lectin Reduces the Oncolytic Vaccinia Virus Induced Toxicity in a Glioblastoma Mouse Model

Abstract: Although oncolytic viruses provide attractive vehicles for cancer treatment, their adverse effects are largely ignored. In this work, rat C6 glioblastoma cells were subcutaneously xenografted into mice, and a thymidine kinase-deficient oncolytic vaccinia virus (oncoVV) induced severe toxicity in this model. However, oncoVV-HddSBL, in which a gene encoding Haliotis discus discus sialic acid-binding lectin (HddSBL) was inserted into oncoVV, significantly prolonged the survival of mice as compared to the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…34 Recombinant VACV has shown therapeutic effects in several murine tumor models, including those of glioblastoma, pancreatic cancer, and melanoma. [35][36][37][38] Interestingly, we found that both WT and recombinant VACV were less replicative in the murine triple-negative breast cancer (TNBC) cell line 4T1, which shows high levels of TTP, 39 both in vitro and in vivo. Furthermore, TNBC cells from different species differ in terms of TTP expression, which affects the replication of recombinant VACV.…”
Section: Discussionmentioning
confidence: 95%
“…34 Recombinant VACV has shown therapeutic effects in several murine tumor models, including those of glioblastoma, pancreatic cancer, and melanoma. [35][36][37][38] Interestingly, we found that both WT and recombinant VACV were less replicative in the murine triple-negative breast cancer (TNBC) cell line 4T1, which shows high levels of TTP, 39 both in vitro and in vivo. Furthermore, TNBC cells from different species differ in terms of TTP expression, which affects the replication of recombinant VACV.…”
Section: Discussionmentioning
confidence: 95%
“…Impotence of cell surface sialylation in tumorigenesis and metastasis was known for a long time [48,49]. The sialic acid-binding lectin from the mollusk Haliotis discus discus, which is also a representative of the C1qDC proteins [30], possesses pronounced antitumor properties [50][51][52]. Other important saccharides for tumorigenic cell surface alteration are mannosides [53].…”
Section: Discussionmentioning
confidence: 99%
“…A number of other Bivalvia C1qDC proteins are also sialic-acid-specific [40,41,43], as well as HddSLB from the gastropod H. discus discus. HddSLB has been tested on several cell lines and exhibited pronounced antitumor activity [42,128,129]. In particular, tumors of epithelial origin such as hepatocellular carcinoma Hep3B, lung cancer A549, non-small cell lung cancer H1299, colorectal adenocarcinoma SW480, as well as leukemia K562/ADR and glioma U87MG were sensitive [128,129].…”
Section: Biomedical Applications Of Invertebrate C1qdc Proteinsmentioning
confidence: 99%